Innovative technologies for the synthesis of pharmaceuticals in transgenic plants - Inshyna, N. (Scientific Progress & Innovations, 2025)
The use of transgenic organisms for the production of pharmaceutical compounds has given rise to a new industry, biopharmaceutical, whose main products are vaccines, monoclonal antibodies, and therapeutic and nutraceutical proteins. The high cost of biopharmaceuticals necessitates the search for and development of new synthesis technologies that will ensure their availability to the general population. The aim of this study was to characterize the current achievements in the field of biopharmaceuticals and to determine the potential of transgenic plants as an alternative means for the production of therapeutic and preventive recombinant proteins. The study used a systematic approach, systematic analysis, and bibliosemantic method to review the literature on the synthesis of pharmaceuticals in transgenic plants. The development of plant genetic engineering has given rise to new methods for the synthesis of biologically active peptides and proteins characterized by better economic efficiency, productivity, and safety than traditional expression systems based on microbial or mammalian cells. Unlike bacteria, plants provide post-translational modification of proteins similar to those in the human body. This enables plants to produce biologically active recombinant human proteins of high quality. To date, transgenic plants have been created that are capable of synthesizing human proteipeptide hormones, enzymes, monoclonal antibodies, interferons, growth factors, cytokines, and microbial antigens for the production of vaccines. The development and improvement of the transient expression system in plants allows the production of pharmaceuticals in a short time, which is important during pandemics. The newest pharmaceuticals have been created on the basis of genetically modified plants: ZMapp, a complex of monoclonal antibodies against Ebola; Covifenz vaccine against SARS-CoV-2; and Eleliso, a drug for the enzyme replacement therapy of Gaucher disease. The production of edible vaccines is a priority area of application of transgenic plants in the pharmaceutical industry. The development and implementation of recombinant protein synthesis technologies based on plant expression systems creates new opportunities to provide humanity with affordable and safe therapeutic and preventive pharmaceuticals.